Development and evaluation of functional “Harukam” jelly gum for oral health in stunted children - Meilla Dwi Andrestian; Naning Kisworo Utami; Aima Insana; Noraini Noraini (AcTion: Aceh Nutrition Journal, 2025)
Snakehead fish (Channa striata) bones exhibited antibacterial activity against cariogenic bacteria, while Banjar Siam orange (Citrus reticulata) provided complementary antibacterial effects. The combination of these ingredients has the potential to be formulated into a functional saliva-stimulating jelly gum to support oral health in stunted children. This study aimed to obtain an optimal formulation of “Harukam” jelly gum as a saliva stimulant for caries prevention. The research was conducted at the Health Polytechnic of the Ministry of Health Banjarmasin and the Industrial Service Standardization Center Banjarbaru, Indonesia, from June to October 2025. A completely randomized design was applied using four concentrations of snakehead fish bone flour: P0 (0%), P1 (1%), P2 (2%), and P3 (3%). Sensory evaluation was performed using the Hedonic Scale, while the chemical composition was determined through proximate analysis. Optimization was determined using the DeGarmo method, and statistical analysis was performed using the Friedman test. The addition of snakehead fish bone flour significantly affected sensory acceptance (p < 0.001) and increased most proximate values, except for carbohydrates. The P1 formulation received the highest preference score. In conclusion, P1 “Harukam” jelly gum showed potential as a functional food to stimulate saliva secretion and support caries prevention in stunted children.